Controls on Soil Organic Matter Degradation and Subsequent Greenhouse Gas Emissions Across a Permafrost Thaw Gradient in Northern Sweden - AminiTabrizi, Roya; Wilson, Rachel M.; Fudyma, Jane D.; Hodgkins, Suzanne B.; Heyman, Heino M.; Rich, Virginia I.; Saleska, Scott R.; Chanton, Jeffrey P.; Tfaily, Malak M. (Frontiers in Earth Science, 2020)
Warming-induced permafrost thaw could enhance microbial decomposition of previously stored soil organic matter (SOM) to carbon dioxide (CO2) and methane (CH4), one of the most significant potential feedbacks from terrestrial ecosystems to the atmosphere in a changing climate. The environmental parameters regulating microbe-organic matter interactions and greenhouse gas (GHG) emissions in permafrost peatlands are however still largely unknown. The objective of this work is to understand controls on SOM degradation and its impact on GHG emissions across the Stordalen Mire, a thawing peat plateau in Northern Sweden. Here, we applied high-resolution mass spectrometry to characterize SOM molecular composition in peat soil samples from the active layers of a Sphagnum-dominated bog and rich fen sites in the Mire. Microbe-organic matter interactions and GHG emissions across the thaw gradient were controlled by aboveground vegetation and soil pH. An increasingly high abundance of reduced organic compounds experiencing greater humification rates due to enhanced microbial activity were observed with increasing thaw, in parallel with higher CH4 and CO2 emissions. Bog SOM however contained more Sphagnum-derived phenolics, simple carbohydrates, and organic- acids. The low degradation of bog SOM by microbial communities, the enhanced SOM transformation by potentially abiotic mechanisms, and the accumulation of simple carbohydrates in the bog sites could be attributed in part to the low pH conditions of the system associated with Sphagnum mosses. We show that Gibbs free energy of C half reactions based on C oxidation state for OM can be used as a quantifiable measure for OM decomposability and quality to enhance current biogeochemical models to predict C decomposition rates. We found a direct association between OM chemical diversity and δ13C-CH4 in peat porewater; where higher substrate diversity was positively correlated with enriched δ13C-CH4 in fen sites. Oxidized sulfur-containing compounds, produced by Sphagnum, were further hypothesized to control GHG emissions by acting as electron acceptors for a sulfate-reducing electron transport chain, inhibiting methanogenesis in peat bogs. These results suggest that warming-induced permafrost thaw might increase organic matter lability, in subset of sites that become wetlands, and shift biogeochemical processes toward faster decomposition with an increasing proportion of Creleased as CH4.